(De)escalating labour conflicts in global production networks: A global framework agreement in the garment sector and its implementation in Bangladesh - Jona Bauer (Südwind-Verlag, 2021)
The garment sector has become the prime example of a global production network (GPN). While multinational corporations (MNCs) in the Global North conduct more profitable processes such as design, marketing and retailing, the production of garments takes place in the countries of the Global South. These labour-intensive production processes are often performed under problematic employment conditions where workers receive low wages and are exposed to health and safety risks. National approaches - either from lawmakers or from workers' collective action - have often failed to improve labour conditions and to secure labour rights due to the global structure of production and the power asymmetries within GPNs. In his Master's thesis, Jona Bauer focuses on so-called 'Global Framework Agreements' concluded by Global Union Federations and Multinational Corporations as a global tool to strengthen labour rights in the context of GPNs. Building on the GPN approach combined with concepts of multi-scalar labour agency and the power resource approach, he shows for one specific GFA of a Swedish retailer applying to Bangladesh, that these agreements can provide an option for workers to address workers' issues through the power of a global buyer. On the other hand, the agreements contain multiple conflicts and are not an instrument for changing power relations within the GPN. This thesis is an important contribution to the discussion on how to reduce or eliminate unsustainable production conditions in GPNs. Similar to the analysed GFA, many instruments such as supply chain laws or technical solutions to increase traceability and transparency do not alter existing power asymmetries within global production networks. Thus, the formation, functioning and limits of such tools and the impact on unequal value distribution and production conditions, and ultimately on power relations should be critically assessed in future research.
Keywords: 330